Development Plan for a Micro-Hydropower Plant at the Suwung Wastewater Treatment Facility - I Made Oka Widyantara; Lie Jasa; Ni Wayan Budiantari; Made Wianda Indiraningtyas (Journal of Renewable Energy and Smart Device, 2026)
This study aimed to analyze the feasibility and design of a Micro Hydro Power Plant (PLTMH) system utilizing wastewater flow at UPTD PAL Provinsi Bali as a renewable energy source to support sustainable energy development and the “Bali Mandiri Energi Bersih 2045” program. The research employed a quantitative engineering design approach through field observations, hydraulic measurements, hydropower calculations, turbine design analysis, electrical power estimation, and preliminary infrastructure planning. Primary data included water discharge, flow velocity, head elevation, pH, and wastewater temperature obtained directly from IPAL Suwung, while secondary data were collected from scientific journals, technical references, and related regulations. The results showed that the wastewater flow at IPAL Suwung has significant hydropower potential with discharge values ranging from 0.2 m³/s to 0.83 m³/s and effective head values between 0.145 m and 0.745 m. Based on the engineering calculations, the proposed Overshot Waterwheel turbine system was capable of generating net electrical power ranging from 0.129 kW under actual minimum conditions to 1.242 kW under maximum engineering design conditions, with estimated annual energy production reaching 9,791.928 kWh. The proposed PLTMH system consists of integrated civil, mechanical, and electrical components, including a cross-flow turbine, pulley transmission system, supporting frame, pillow block bearings, permanent magnet generator, and electronic load control system, with a total estimated project cost of IDR 197,585,297. These findings show that the development of PLTMH at IPAL Suwung is technically feasible, economically reasonable, and environmentally sustainable for supporting renewable energy utilization in wastewater treatment facilities.